Characterization of the genomic landscape and actionable mutations in Chinese breast cancers by clinical sequencing - Guan-Tian Lang (Nature Portfolio, 2020)
Chinese breast cancer patients have not been well represented in clinical sequencing studies. Here the authors analyse the mutational landscape of 1,134 Chinese breast cancer patients, finding actionable targets and a higher prevalence of p53 and Hippo pathway mutations compared to Western cohorts.